2019
DOI: 10.1016/j.ecolind.2018.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Use of botanical insecticides for sustainable agriculture: Future perspectives

Abstract: Recent decades have witnessed major growth in the use of agrochemicals worldwide,for maximizing the food production for a rapidly growing human population. However, the indiscriminate use of these substances especially the pesticides has led to the accumulation of toxic residues in food, soil, air, and water, as well as the development of resistance in pests. Moreover, pesticides affect soil enzymes, which are essential catalysts that govern soil quality. In order to meet the food security, it is necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
144
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(176 citation statements)
references
References 205 publications
3
144
0
5
Order By: Relevance
“…A study in Nicaragua found that plots sprayed with synthetic insecticides had low numbers of generalist predators including spiders compared with a no insecticides application treatment 7 . The current study therefore supports the notion that aqueous plant extracts are relatively harmless to natural enemies [49][50][51] and can be integrated with biological pest control unlike synthetic insecticides such as Attack which has deleterious effects on natural enemies. This insecticide (Attack) is a semi-synthetic derivative of the natural product abamectin in the avermectin family 52,53 .…”
Section: Discussionsupporting
confidence: 81%
“…A study in Nicaragua found that plots sprayed with synthetic insecticides had low numbers of generalist predators including spiders compared with a no insecticides application treatment 7 . The current study therefore supports the notion that aqueous plant extracts are relatively harmless to natural enemies [49][50][51] and can be integrated with biological pest control unlike synthetic insecticides such as Attack which has deleterious effects on natural enemies. This insecticide (Attack) is a semi-synthetic derivative of the natural product abamectin in the avermectin family 52,53 .…”
Section: Discussionsupporting
confidence: 81%
“…Essential oils exhibit a wide spectrum of pesticidal activities from lethal to sublethal effects against a wide range of insects and mites [7,24,28]. Pesticidal effects of essential oils extracted from different plant families such as Apiaceae, Asteraceae, Chenopodiaceae, Cupressaceae, Lamiaceae, Lauraceae, Myrtaceae, Zingiberaceae, Umbelliferae, and Geraniaceae have been documented [7,9,29,30].…”
Section: Plant Essential Oils and Their Pesticidal Activitiesmentioning
confidence: 99%
“…Continuing the long quest for identifying bioactive compounds with insecticidal/insect deterrent activity [49][50][51][52][53][54][55][56], we hypothesized that the pericarp extracts may also negatively affect herbivore growth and development. We tested this hypothesis using the tobacco hornworm caterpillar (Manduca sexta L.), a model herbivore for examining growth and development traits (easy to rear in lab with short lifecycle and distinct growth stages) [8,9,57,58].…”
Section: Introductionmentioning
confidence: 99%